ANALISA KEPUASAN PELANGGAN ATAS KUALITAS PELAYANAN JASA PADA PEMEGANG KARTU KREDIT EVERYDAY BANK MANDIRI DI JAKARTA - Imawan, Zera N.; Sucento, Bun (Bina Nusantara University, 2009)
Customer satisfaction is a target or object that must be achieved by every companies. For those achievements, we could see from services that given and quality of product that oferred by. The objective of this research is to measure and know the customer satisfaction, and how far the relation of the productivity level from Bank Mandiri Everyday Credit Card agains Customer Interest Level.Research method used survey research method. Sample from 100 people with primary and secondary data. After that, we used validitty test, GAP analysis, and cartesius diagram analysis to see the gap between interest level and reality level with Bank Mandiri productivity. Analysis Result from GAP method is -0,1 that means customer satisfaction of the holder Bank Mandiri Everyday credit card is satisfy enough. But Bank Mandiri must maintain some factors to make customer keep using Bank Mandiri services and never changeover to other bank.